PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN CV. PRIMA INDONESIA TANGERANG SELATAN - Ghina khoiriyah; Dede Andi (Journal of Research and Publication Innovation, 2025)
This study aims to determine and analyze the effect of work discipline and physical work environment on the employee performance of CV. Prima Indonesia - South Tangerang. The population in this study were employees of CV. Prima Indonesia-South Tangerang as many as 57 people. The sampling method in this study uses saturated sample technique, the data analysis method used is descriptive statistical test, instrument test (validity test and reliability test), classical assumption test (normality test, multicolinerity test, and heteroscedasticity test), correlation test, coefficient of determination test, regression test, and hypothesis testing using SPSS Ver.25. The results of this study are Work Discipline has a significant effect on employee performance with a coefficient of determination of 48.5%, and hypothesis testing obtained t value> t table or (7,190> 2.004). Physical Work environment has a significant effect on employee performance with a coefficient of determination of 38.8%, and hypothesis testing obtained t value> t table or (5,902> 2,004). Work discipline and Physical work environment have a significant effect on employee performance simultaneously with the regression equation Y = 3.510 + 0.523X1 + 0.2342X2, The coefficient of determination is 52.7% while the remaining 47.3% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (30.130> 3.170)